Research trend of MRI application for lumbar disc degeneration with low back pain: a bibliometric analysis - Saeed, Azzam; Shao, Haoyue; Hezam, Kamal; Liu, Chaoxu; Zhang, Qiya; Tang, Xiangyu (Frontiers in Neurology, 2024)
Background Low Back Pain (LBP) is a pervasive and complex musculoskeletal condition affecting over 80% of the global population. Lumbar Disc Degeneration (LDD) significantly contributes to LBP, and MRI is crucial for its diagnosis and understanding. This study aimes to provide a comprehensive bibliometric analysis of MRI research on LDD with LBP, shedding light on research patterns, collaborations, and potential knowledge gaps. Methods A comprehensive online search was conducted in the Scopus database to retrieve published literature on LDD with LBP. Bibliometric analysis was conducted to assess publication patterns, co-authorship networks, keyword co-occurrence, and co-citation analysis within the MRI applications for LDD research domain. Bibliometric analysis tools such as VOSviewer and the R package “bibliometrix” were utilized for quantitative assessments. Results A total of 1,619 publications related to MRI and LDD were analyzed. The analysis indicated a consistent annual growth rate of 4.62% in publications related to MRI and lumbar disc degeneration, reflecting a steady increase in research output over the past two decades. The USA, China, and Japan emerged as leading contributors. “SPINE“, “European Spine Journal“, and “Spine Journal” were the most productive journals in this domain. Key research themes identified included lumbar spine, low back pain, and magnetic resonance imaging. Network visualization shows that low back pain and magnetic resonance imaging were the most widely used keywords. Conclusion The comprehensive bibliometric analysis of MRI applications for Lumbar Disc Degeneration offers insights into prevailing research patterns, highlights key contributors and journals, and identifies significant research themes. This study provides a foundation for future research efforts and clinical practices in the field, ultimately contributing to the advancement of patient care for individuals suffering from LDD and associated Low Back Pain.